2014
DOI: 10.1093/ndt/gfu051
|View full text |Cite
|
Sign up to set email alerts
|

Plasma inflammatory and apoptosis markers are associated with dialysis dependence and death among critically ill patients receiving renal replacement therapy

Abstract: Elevated plasma concentrations of inflammatory and apoptosis biomarkers are associated with RRT dependence and death. Our data suggest that future interventions should investigate broad-spectrum immune-modulation to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 38 publications
0
59
2
1
Order By: Relevance
“…Our recent work suggests that higher circulating concentrations of pro-and anti-inflammatory cytokines and apoptosis markers found in patients at the time of initiation of RRT are independently associated with nonrecovery of renal function and death. Specifically, we found that IL-6, IL-8, IL-10, IL-18, macrophage migration inhibitory factor (MIF), and TNF receptor-I (TNFR-I) and TNFR-II were associated with both reduced survival and renal recovery (3). Death receptor-5 (DR-5) was also associated with reduced survival (3).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our recent work suggests that higher circulating concentrations of pro-and anti-inflammatory cytokines and apoptosis markers found in patients at the time of initiation of RRT are independently associated with nonrecovery of renal function and death. Specifically, we found that IL-6, IL-8, IL-10, IL-18, macrophage migration inhibitory factor (MIF), and TNF receptor-I (TNFR-I) and TNFR-II were associated with both reduced survival and renal recovery (3). Death receptor-5 (DR-5) was also associated with reduced survival (3).…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, we found that IL-6, IL-8, IL-10, IL-18, macrophage migration inhibitory factor (MIF), and TNF receptor-I (TNFR-I) and TNFR-II were associated with both reduced survival and renal recovery (3). Death receptor-5 (DR-5) was also associated with reduced survival (3). High-intensity RRT has been proposed to clear inflammatory markers in patients with AKI and improve outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…47 Our study also expands on the literature of these cytokines in the perioperative setting, which has generally been conducted with small cohorts, in single-center settings, and with lack of defined hard outcomes. While some larger studies have reported inconsistent results, 48,49 a majority of these were not undertaken in the perioperative setting. The discrepancies may primarily be due to the complications by other underlying abnormalities in the patient cohorts, such as sepsis or other critical illnesses.…”
Section: J Am Soc Nephrol 26: 3123-3132 2015mentioning
confidence: 99%
“…More than half of patients receiving RRT die, and only a third are alive and independent of RRT by 2 months after acute illness (1). Despite decades of research, no specific treatment has improved outcomes from severe AKI.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that higher circulating concentrations of plasma inflammatory (IL-6, -8, -10, and -18 and macrophage migration inhibitory factor) and apoptosis (tumor necrosis factor receptor (TNFR) I and II and death receptor-5) biomarkers were strongly associated with RRT dependence and death using the Biologic Markers of Recovery for the Kidney (BioMaRK) study cohort (1). BioMaRK was as an ancillary study to the Veterans Affairs (VA)/National Institutes of Health (NIH) Acute renal failure Trial Network (ATN) study (3).…”
Section: Introductionmentioning
confidence: 99%